Pemanfaatan Rumput Laut Kendal sebagai POC untuk Meningkatkan Produksi Tanaman Bayam (Amaranthus tricolor L.): Utilization of Inedible Seaweed as Liquid Organic Fertilizer for Enhancing Spinach Plant (Amaranthus tricolor L.) Production - A. Farhanah; Ismail Tandi; Rezki Maya Musfira; Jabal Rahmat Ashar (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2022)
There have not been many studies using inedible seaweed as a liquid organic fertilizer (LOF), although it contains nutritional components that have benefits for growth and production of plants. This study was done to determine the effectiveness of liquid organic fertilizer application made from inedible seaweed (Sargassum polycystum) on the productivity of spinach plant (Amaranthus tricolor L.). This study analysis used Randomized Block Design (RBD) having 4 treatments (control, LOF 150 mL/L water, LOF 250 mL/L water, and LOF 150 mL/L water) and replicated 4 times, resulting 16 experimental plots. The result showed that the treatment by providing 250 mL/L inedible seaweed liquid organic fertilizer effectively gave the highest yield of spinach than all treatments with height 40.5 cm, leaves number of 32, wet weight of 15.08 g, and the productivity of green spinach plants reaching 4.31 tons/ha. By this study, conclution is the application of inedible seaweed liquid fertilizer 250 mL/L water giving significant effect for spinach growth and production.